ANALISIS RESPON PENGGUNA TERHADAP DIGITALISASI SOP PENGGUNAAN ALAT LABORATORIUM MELALUI PENGEMBANGAN KONTEN PADA WEBSITE - Puput Marlisa; Nursiah Nursiah (Jurnal Binagogik, 2026)
Digitalization plays an important role in improving laboratory management by providing more efficient access to information, facilitating the use of laboratory equipment, and enhancing the quality of laboratory services. However, access to Standard Operating Procedures (SOPs) and work instructions for laboratory equipment has often been limited because the information is still provided through conventional methods. This study aimed to analyze users’ responses to the digitalization of SOPs for laboratory equipment through the development of website-based content at the Faculty of Agriculture, Malikussaleh University . A descriptive quantitative approach was employed in this study. The participants were 22 respondents, consisting of 16 lecturers and 6 students. Data were collected through a questionnaire distributed using Google Forms, consisting of 18 statements measured on a five-point Likert scale. The data were analyzed descriptively based on the distribution and percentage of responses in each category. The findings indicate that the digitalized SOPs developed through the website were well received by users and considered feasible for supporting laboratory practical and research activities. Overall, the website-based digitalization of laboratory equipment SOPs provides an accessible and useful source of information that can support practical and research activities while improving the efficiency and quality of laboratory services.